2008 Annual Reliability and Maintainability Symposium 2008
DOI: 10.1109/rams.2008.4925845
|View full text |Cite
|
Sign up to set email alerts
|

A historical survey with success and maturity estimates of launch systems with RL10 upper stage engines

Abstract: Pratt & Whitney's RL10 engine line has a long and rich history, beginning in 1958 and continuing today. This paper provides a historical summary of launch vehicles using RL10 engine derivatives dating from 1962-2005. The historical launch data is used to derive baseline launch success rates and growth curves for vehicles configured with RL10 engines in the upper stage. Because it was the first liquid hydrogen fueled rocket engine, the RL10 engine launch history provides a unique opportunity to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…When a more specific subset of the data is investigated (Go, 2008) the situation is a bit better. As can be seen in Fig.…”
Section: Maturity Associated Reliability Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…When a more specific subset of the data is investigated (Go, 2008) the situation is a bit better. As can be seen in Fig.…”
Section: Maturity Associated Reliability Growthmentioning
confidence: 99%
“…Most recently the classic problem of reliability growth has been addressed by a number of authors. These investigations have addressed the general problem and the specific problems as they were observed in the aerospace industry both in aircraft (Walls, Quigley, & Marshall, 2006) and in space launcher stages (Go, 2008). Immaturity becomes a particular problem as systems become more complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very often, it is observed that the most critical failures in a liquid propulsion system are manifested at the interfaces between elements of the integrated vehicle [15]. Understanding the physics of the rocket engine allows one to investigate the integrated propulsion system to identify system level synergistic characteristics.…”
Section: Integrated Stage Behavior-main Propulsion System and Engine mentioning
confidence: 99%
“…All Centaur historical data in this paper results from a combined analysis of the data provided by [8], [9], [10], [11] and [12].…”
Section: Introduction To Centaur Case Studymentioning
confidence: 99%